2014
DOI: 10.1186/1471-244x-14-63
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis of the determinants of the global assessment of functioning in an inpatient population

Abstract: BackgroundThe Global Assessment of Functioning (GAF) is a widely used measure of psychiatric symptoms and functioning, yet numerous concerns persist about its reliability and validity. The objective of this study was to determine the extent to which GAF scores reflect physician-related differences in addition to information about patients.MethodsThis is a secondary analysis of clinical data collected between 2005 and 2010 from inpatients at a psychiatric hospital (N = 1,852). Multilevel modeling was used to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The first author read each patient's electronic record, made an abstract of the clinical condition and the psychosocial functioning, then filled in the first and second forms. All cases were subsequently reviewed and discussed by the research team, which made the final consensual decision on outcome Good outcomePatient in remission, as assessed either by his/her treating physician, according to the discharge summary when applicable, or from descriptions of the patient's functional status (such as being back at school or work, living independently, etc.…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…The first author read each patient's electronic record, made an abstract of the clinical condition and the psychosocial functioning, then filled in the first and second forms. All cases were subsequently reviewed and discussed by the research team, which made the final consensual decision on outcome Good outcomePatient in remission, as assessed either by his/her treating physician, according to the discharge summary when applicable, or from descriptions of the patient's functional status (such as being back at school or work, living independently, etc.…”
Section: Methodssupporting
confidence: 86%
“…All cases were subsequently reviewed and discussed by the research team, which made the final consensual decision on outcome. 24 A.…”
Section: Instrumentsmentioning
confidence: 99%
“…In addition to the GAF and the CGI to indicate illness severity, we also considered a suicide attempt during lifetime, the existence of legal guardianship, and the cumulative length of psychiatric hospital stays during the indexed year. In a multilevel analysis of the determinants of GAF, Urbanoski et al demonstrated, after controlling for patient-level predictors that only 7 % of the residual variance in admission GAF and 8 % of the residual variance in change scores was accounted by assessments of an individual patient made by different psychiatrists; these results lend support to the utility of GAF for drawing comparisons between patients sampled from a large institution [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…There were no dropouts, but thirty-one participants didn't have complete data at discharge, because they didn't want to meet ACT teams again after discharge, end of care was decided by phone, or end of care was not clearly formalized. scale has an excellent interrater reliability and nomothetic validity [26,27].…”
Section: Participantsmentioning
confidence: 99%